The Transportation Cooperation Between Northeast China and the Russian Far East Under the Russia-Ukraine War - Yu Yan (Journal of World Economy, 2024)
The logistics and transportation system of Russia and the world was greatly affected by the 2022 Russia-Ukraine war and the sanctions under the war. Under such circumstances, Sino-Russian cooperation in cross-border transportation is of great significance for the operation of international logistics system and the high-quality cooperation between China and Russia. The aim of this research is to find feasible paths for the transportation cooperation between Northeast China and Russian Far East by analyzing the current situation and existing problems in international transportation cooperation between the two regions. It was found that the current feasible paths of transportation cooperation between Northeast China and Russian Far East include: (1) carrying out transportation cooperation through “pivot cities”; (2) strengthening transportation cooperation by Russian Far East’s Territories of Advanced Development; (3) seizing the new opportunities of Harbin’s opening up to the north to promote international transportation cooperation with Russia; (4) developing transportation cooperation through the linking cooperation between the “Belt and Road” and the “Eurasian Economic Union”.